Analytical measurement uncertainty of food carotenoid determination - Dias, M. Graça (2012)
Resumo publicado em: EURACHEM/CITAC 2011 workshop: Recent Developments in Measurement Uncertainty, 6‐7 June 2011: book of abstrats, p. P - 25 [Disponível em: http://eurachem2011.fc.ul.pt/pdf/Eurachem_CITAC2011-BookofAbstracts.pdf]